Infinitude in Religion: When One Life Is Not Enough - Rezende, Eliane Garcia; Lodovici, Flamínia Manzano Moreira; Concone, Maria Helena Villas Bôas (Revista Kairós-Gerontologia, 2014)
Death can be interpreted as a social and historical product. In the context of spirituality death is constructed as a transcendence of life and becomes a passage to the other side, while establishing a continuity of life in the world unseen. Books self-described as Spiritists and/or Spiritualists published in Portuguese within Brazil’s prevailing religious pluralism tell the epopee of spirits, whose spiritual evolution requires numerous reincarnations aimed at ongoing changes toward its improvement. In this process, death is nothing but a passage in the Life of a spirit who gradually progresses through stages to erase its finitude from an "embodied" to a "disembodied" spirit.